An investigation into university extra-curricular enterprise support provision. Issue 8 (9th November 2015) - Preedy, Sarah; Jones, Paul
Abstract : Purpose: – The employment market means students need to be equipped with wide-ranging enterprising skills and experience. With small- and medium-sized enterprises crucial to the health of the UK economy providing graduates with the skills to start-up their own business is also of increasing pertinence. The purpose of this paper is to analyse universities' provision and delivery of student support in developing their enterprise knowledge, skills and experience outside of the curriculum. Design/methodology/approach: – An e-survey of universities alongside three follow-up semi-structured interviews with participants and an in-depth case study was gathered. The e-survey quantified what enterprise support activities the sample institutions currently offered and the interviews and case study examined the delivery of those activities through the perceptions of university staff/students. Findings: – The respondents offered a range of enterprise support activity outside of the curriculum but delivery was hindered by a limited means to track proceedings. Support activities were predominantly concentrated both in delivery and receipt within business schools rather than across departments. Support typically consisted of networking events, business advice sessions and workshops as opposed to intensive provisions such as incubation space or start-up loans. The presence and influence of student-led enterprise groups was apparent. Practical implications: – The results will inform those staff involved in the planning and delivery of enterprise support activity at UK universities. Originality/value: – This research extends a limited literature mapping extra-curricular enterprise support provision at universities with qualitative data on the delivery of these activities as perceived by staff/students.